Flame retardant properties and mechanism of PLA/P-PPD -Ph /ECE conjugated flame retardant composites - Tan, Yanyan; Zhang, Daohai; Xue, Yu; Zhan, Xiao; Tan, Fang; Qin, Shuhao (Frontiers in Chemistry, 2023)
In this article, 4, 4'-1'',4''-phenylene-bis[amido-(10'' ''-oxo-10'''-hydro-9'''-oxa-10'''λ5-phosphafi-10'''-yl)-methyl]-diphenol (P-PPD-Ph) was synthesized by a two-step synthesis, followed by the addition of various levels of epoxy chain extender (ECE) with 5 wt% of P-PPD-Ph The PLA/P-PPD-Ph/ECE conjugated flame retardant composites were produced by co-extrusion into poly(lactic acid) (PLA). The chemical structure of P-PPD-Ph was characterized by FTIR, 1H NMR and 31P NMR tests, demonstrating the successful synthesis of the phosphorus heterophilic flame retardant P-PPD-Ph. The structural, thermal, flame retardant and mechanical properties of the PLA/P-PPD-Ph/ECE conjugated flame retardant composites were characterised using FTIR, thermogravimetric analysis (TG), vertical combustion testing (UL-94), limiting oxygen index (LOI), cone calorimetry, scanning electron microscopy (SEM), elemental energy spectroscopy (EDS) and mechanical properties testing. The structural, thermal, flame retardant and mechanical properties of PLA/P-PPD-Ph/ECE conjugated flame retardant composites were characterised. The results showed that with the increase of ECE content, the residual carbon rate of the composites increased from 1.6% to 3.3%, and the LOI value increased from 29.8% to 32.6%. The cross-linking reaction between P-PPD-Ph and PLA and the increase of reaction sites led to the generation of more phosphorus-containing radicals on the PLA molecular chain, which strengthened the cohesive phase flame retardant effect of PLA flame retardant composites, and The bending strength, tensile strength and impact strength were all improved.